Structural testing and numerical modelling of T-joints between cold-formed S690 circular hollow sections under brace in-plane bending. (1st January 2022) - Hu, Yi-Fei; Chung, Kwok-Fai; Ban, Huiyong; Nethercot, David A.
Graphical abstract: Highlights: Six T-joints between S690 CFCHS were tested under brace in-plane bending. Both monotonic and cyclic actions were applied to these joints. All joints failed with a fracture in the heat-affected zones of the braces. An integrated numerical modelling approach was developed to examine these joints. Heat transfer, thermomechanical and structural analyses were performed. Residual stresses caused little strength reductions in these T-joints. Abstract: This paper presents a comprehensive investigation into the structural behaviour of T-joints between high strength S690 cold-formed circular hollow sections (CFCHS) under brace in-plane bending, and deformation characteristics of these T-joints under both monotonic and cyclic actions are examined experimentally and simulated numerically. These T-joints between S690 CFCHS were found to deform with a high level of resistances and ductility under both monotonic and cyclic actions. Through an integrated numerical modelling approach developed by the authors, advanced three-dimensional finite element models of CFCHS with solid elements were established. With a proper definition of weld collars at the brace/chord junctions of the T-joints between S690 CFCHS with different diameters and thicknesses, these models were readily adopted to perform a heat transfer analysis, a thermomechanical analysis and a structural analysis sequentially with compatible element types and meshes. Hence, the effects of the welding-induced residual stresses at the welded brace/chord junctions onto the structural behaviour of these T-joints were readily assessed. Consequently, these advanced models are demonstrated to be able to predict rationally deformation characteristics of these T-joints between S690 CFCHS under monotonic and cyclic actions of brace in-plane bending with a high degree of structural accuracy.